STOP Pain Project—Opioid Response in Pediatric Cancer Patients and Gene Polymorphisms of Cytokine Pathways - Crescioli, Giada; Lombardi, Niccolò; Vagnoli, Laura; Bettiol, Alessandra; Giunti, Laura; Cetica, Valentina; Coniglio, Maria Luisa; Provenzano, Aldesia; Giglio, Sabrina; Bonaiuti, Roberto; Mugelli, Alessandro; Aricò, Maurizio; et al. (Pharmaceutics, 2022)
Moderate to severe cancer pain treatment in children is based on the use of weak and strong opioids. Pharmacogenetics play a central role in developing personalized pain therapies, as well as avoiding treatment failure and/or intolerable adverse drug reactions. This observational study aimed to investigate the association between IL-6, IL-8, and TNFα genetic single nucleotide polymorphisms (SNPs) and response to opioid therapy in a cohort of pediatric cancer patients. Pain intensity before treatment (PIt0) significantly differed according to IL-6 rs1800797 SNP, with a higher PI for A/G and G/G individuals (p = 0.017), who required a higher dose of opioids (p = 0.047). Moreover, compared to G/G subjects, heterozygous or homozygous individuals for the A allele of IL-6 rs1800797 SNP had a lower risk of having a PIt0 > 4. Dose24h and Dosetot were both higher in G/G individuals for TNFα rs1800629 (p = 0.010 and p = 0.031, respectively), while risk of having a PIt0 > 4 and a ∆VAS > 2 was higher for G/G subjects for IL-6 rs1800795 SNP compared to carriers of the C allele. No statistically significant association between genotypes and safety outcomes was found. Thus, IL-6 and TNFα SNPs could be potential markers of baseline pain intensity and opioid dose requirements in pediatric cancer patients.